APLIKASI PELAYANAN PUBLIK PADA UNIT PELAKSANA PELAYANAN TERPADU SATU PINTU (PTSP) BERBASIS WEB - Anggi Puspita Sari; Dede Dudik Kurnia; Biktra Rudianto (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2021)
The application process for KPR (Home Ownership Loan), Introduction to Party Permits and Residence Domicile Information in the Integrated Service Implementation Unit of One Door Cengkareng Barat Village is still done manually so that it is less fast and efficient in the implementation of services. The creation of this web-based public service application is designed to help the Integrated Service Implementation Unit one door Village case study Of West Cengkareng in carrying out services to the community in the area of West Cengkareng Village. This application can make it easier for citizens to obtain the desired cover letter. This application makes it easy for officers to convey information on the types of cover letters and requirements through a web browser and citizens can access anywhere while connected to the internet. In addition, this application can provide convenience to residents because they do not have to come to the village to ask about the requirements of the KPR (Home Ownership Credit), Party Permit Cover Letter and Certificate of Residence Domicile that is desired because everything is already contained in the website.